Method and device for manufacturing artificial graphite negative electrode material by infiltrating porous carbon blank with molten steel

By performing cascaded operations of high-temperature incubation and low-temperature incubation in low-carbon molten steel, the problems of high energy consumption and uneven cladding of traditional graphitization processes are solved, and efficient and stable water infiltration of porous carbon billet steel is achieved to produce artificial graphite The negative electrode material reduces iron powder consumption and production cycle, and improves the product's capacity and first-term effect.

CN119306213APending Publication Date: 2025-01-14SHENZHEN GANGYU CARBON CRYSTAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310871826.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Traditional high-temperature graphitization and coating processes have problems such as high energy consumption, long production cycle, high cost, uneven surface coating layer, and uneven SEI film growth. In addition, iron powder consumes a lot and corrosion removes iron in high and low-temperature iron in the method of fertilizing high and low-temperature iron. , low production efficiency.

Method used

The cascade operation of high-temperature incubation and low-temperature incubation is carried out by using low-carbon molten steel. The infiltration of porous carbon billets in the molten steel is driven by gas pressure differential to form artificial graphite powder with microporous structures, realizing graphitization and coating deposition on the same equipment Complete it in one go, reducing iron powder consumption and simplifying the process.

Benefits of technology

It has achieved economic and environmentally friendly production, low energy consumption, fast production cycle, high raw material utilization rate, stable equipment operation, large capacity of artificial graphite products, high first-term efficiency, and stable mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306213A_ABST
    Figure CN119306213A_ABST
Patent Text Reader

Abstract

The invention provides a method and a device for manufacturing an artificial graphite negative electrode material by adopting gas pressure difference to drive molten steel to infiltrate a porous carbon blank and realizing high-temperature inoculation and low-temperature inoculation, the molten steel with low carbon content and good wettability is adopted as a process medium, and the preheated porous carbon blank is fed into the molten steel; the preparation method comprises the following steps: carrying out high-temperature inoculation micro-dissolution treatment at the temperature of 1550-1750 DEG C, and carrying out cascade low-temperature inoculation treatment at the temperature of 1250-1450 DEG C after cooling, so as to improve the graphitization degree, improve the specific surface area and improve the SEI film forming uniformity. According to the present invention, the porous carbon blank in the piston can be rapidly and completely infiltrated by the molten steel, or the saturated molten iron can be extruded into the lower crucible from the treated porous carbon blank, the manufacturing energy consumption is low, the production time is short, the molten steel loss is low, and the obtained artificial graphite powder has characteristics of good quality consistency, high product gram volume and high first efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion secondary batteries, in particular to artificial graphite negative electrode materials used therein. Background Art

[0002] As the negative electrode active material of lithium-ion batteries, graphite has high specific capacity, low reduction potential, good electrochemical reversibility, low volume expansion rate, high electronic conductivity, and a wide range of raw material sources. It is currently the negative electrode material used in lithium-ion secondary batteries.

[0003] Commercial graphite negative electrode materials mainly include artificial graphite and natural graphite. The advantages of natural graphite are low cost and high compaction density. The main disadvantages are: (1) The surface of natural graphite powder is rough, with many active sites and large specific surface area. During the first charge and discharge, the process of forming the SEI film on the surface of the negative electrode active material consumes a lot of lithium resources, resulting in low first charge and discharge efficiency, which is referred to as low first efficiency in the industry. (2) Natural graphite has obvious polycrystalline anisotropy, and the thickness of SEI after reaction and growth on the powder surface is uneven. The thicker SEI film will be thicker during the battery charge and discharge cycle. There are cracks and even peeling, which will continuously consume lithium sources and affect the cycle life of the battery; (3) The obvious anisotropy of natural graphite powder will also make it difficult for the volume expansion of the negative electrode material to offset each other during charging and discharging. The battery is prone to swelling, resulting in large fluctuations in the distance between the electrode groups and a rapid decrease in the battery cycle life; (4) The anisotropy of natural graphite powder polycrystals also means that lithium ions can only be inserted or removed from certain end faces of natural graphite powder polycrystals, resulting in a small effective area for insertion or removal, poor battery charge and discharge rate characteristics, and easy lithium precipitation during fast charging, resulting in poor battery safety.

[0004] At present, the mainstream of power battery and energy storage battery industry is to use artificial graphite powder as negative electrode active material, such as all mesophase carbon microspheres or calcined needle coke as raw materials, high temperature graphitization treatment in the high temperature range of 2900-3100℃, and crushing and shaping after cooling to obtain artificial graphite powder. Compared with the anisotropic crystal orientation of the crystal structure of flaky natural graphite powder, the crystal orientation of the polycrystalline structure of artificial graphite powder presents better isotropic characteristics. The surface of the powder is relatively smooth, the active sites on the surface of the powder are relatively few, the specific surface area is small, the initial efficiency is higher than that of natural graphite, and the cycle life is longer. Long life, good rate characteristics. The main disadvantage of artificial graphite powder as anode material is that artificial graphite must be subjected to high-temperature graphitization treatment, which has a long processing cycle, high energy consumption and high cost. The high-temperature graphitization temperature of traditional artificial graphite is as high as 2900-3100℃. The main technical principle of increasing the graphitization degree of traditional artificial graphite is to use the thermal diffusion of carbon atoms at high temperature to re-participate in crystallization to increase the graphitization degree of the graphite precursor and increase the gram capacity. The high-temperature graphitization device usually adopts the classic Acheson graphitization furnace. The raw material powder of the graphite precursor is usually loosely packed in the graphite crucible in a non-compacted state, and the tap density is generally less than 1.15g / cm 3 ; Carbon-based resistor particles are filled between graphite crucibles, and 70-80% of the heating heat is used for these graphite crucibles, resistor materials, insulation materials and other process auxiliary materials. In order to produce uniform products, the heating and insulation time takes nearly 15 days, the cooling time is nearly 10 days, and the processing cycle of one furnace is nearly one month. The overall energy consumption is high, the energy utilization rate is low, the processing cycle is long, and the capital occupation cycle is long, which has become a bottleneck link in reducing the cost of artificial graphite.

[0005] As a long-life negative electrode material used in power batteries and energy storage batteries, in order to improve the uniformity of SEI film growth and increase the initial efficiency and cycle life of the battery, some artificial graphite powders adopt a core-shell structured coated product structure, such as using carbon precursors such as asphalt or furfural resin to coat and modify natural graphite powder or needle coke powder, and then perform medium-temperature carbonization or medium-temperature graphitization treatment, and then crush and grade to manufacture coated core-shell structured artificial graphite powder, in order to obtain a carbon material surface layer mainly composed of amorphous carbon with low crystallinity and low graphitization degree, in order to reduce the thickness of the SEI film formed by the reaction when the powder surface initially contacts the electrolyte; traditional artificial graphite The coating process has the following disadvantages: (1) The process is complex, the product manufacturing cycle is long, and the overall energy consumption is relatively high; (2) The interface strength between the shell and the core of the coated artificial graphite powder material is limited. When the negative electrode is manufactured during strong rolling, the coating shell is easily crushed, resulting in the battery's initial efficiency being still unsatisfactory, the cycle life has quality fluctuations, and the battery consistency needs to be improved; (3) The uniformity of the coated amorphous carbon layer is difficult to control. After coating and high-temperature carbonization, a crushing process is required. The broken surface of the powder formed after crushing has a high reaction activity. The coating layer formed after crushing is microscopically uneven, which affects the specific surface area and initial efficiency of the powder, and the SEI film has poor film formation uniformity.

[0006] The traditional method of manufacturing artificial graphite negative electrode materials by high-temperature graphitization and coating followed by carbonization / crushing / grading has the disadvantages of high energy consumption, long production cycle, high cost, uneven surface coating, and uneven SEI film growth, and needs to be improved.

[0007] The inventor proposed in Chinese patent application CN202210235095.X a method for manufacturing an artificial graphite negative electrode material by cold-pressing a graphite precursor powder together with iron powder, then performing a medium-temperature graphitization treatment at 1600-2200°C, and crushing the powder after cooling for pickling and iron removal; in CN202210281433.3, a method for pre-pressing a graphite precursor powder, then laminating it with an iron plate, performing medium-temperature graphitization using molten iron at 1500-2200°C, and removing iron from the cooled block by electrolytic corrosion or chemical corrosion to obtain an artificial graphite negative electrode material; in CN202210500309.1, a method for hot-pressing a graphite precursor powder with iron powder having a carbon content of less than 2% and asphalt powder into a cylindrical blank, and then laminating it with a steel plate, is proposed. A method for manufacturing artificial graphite negative electrode material by molten iron-assisted graphitization at 1700-2200°C, and electrolytic turning or acid leaching is also performed to remove iron after the block is cooled; CN202210690493.0 proposes hot pressing of graphite precursor powder with iron powder having a carbon content of less than 4% and asphalt powder binder powder, and then using pulse current for internal heating to achieve molten iron-assisted medium-temperature graphitization, and finally the treated block is crushed and chemically corroded to remove iron; the above methods of graphitizing graphite precursor powder at medium temperature using iron powder as a process medium have the disadvantage that a large amount of iron powder is consumed in order to obtain artificial graphite powder, and the work requirements for corroding and removing iron from the block after medium-temperature graphitization are also relatively high, and the manufacturing cost and production efficiency are not satisfactory enough.

[0008] The inventor proposed a technical solution for manufacturing artificial graphite negative electrode materials by using a high-low temperature molten iron inoculation method in Chinese invention patent applications CN202210708922.2, CN202210702022.7, CN202210889452.4, CN202310603657.6, and CN202310735352.0; the basic technical idea is to use high-temperature molten iron as a process medium to preferentially dissolve the highly active carbon on the surface of the carbon powder and the amorphous carbon at the grain boundaries in the polycrystals, and to reduce the saturated solubility of carbon in molten iron during the cooling process and low-temperature inoculation, so as to precipitate carbon from the molten iron to form an artificial graphite powder with a coated core-shell structure, and to use high-low temperature molten iron as a process medium. The technical purpose is to reduce the large amount of iron consumed in the manufacture of artificial graphite negative electrode materials by the powder metallurgy pressing method using iron powder and graphite precursor powder as mentioned in the previous section; CN202210708922.2 proposes a technical solution of using inert gas to blow the graphite precursor powder raw materials into molten iron, and incubate them at high temperature in the high temperature range of 1750-2000°C. The initial carbon content of the molten iron is higher than 4%, and the temperature is reduced to 1250-1600°C for low-temperature incubation; this solution uses gas blowing to transport carbon powder raw materials, which results in a large consumption of inert gas, and the raw material powder is not easy to preheat. There is a strong cooling effect on the molten iron when feeding, and the speed of raw material feeding in production is suppressed; in addition, there is a safety hazard of carbon powder flying to the outside of the graphite crucible causing an electrical short circuit. CN202210702022.7 and CN202210889452.4 propose a technical solution of using the negative pressure at the bottom of the auxiliary piston to adsorb the steel barrel filled with graphite precursor powder raw materials to deliver the materials into the molten iron, and using the main / auxiliary pistons to jointly realize the functions of pressing the carbon powder in the molten iron for high-temperature incubation and low-temperature incubation. In the discharging link, when the powder material is discharged to the outside of the vacuum furnace by negative pressure suction-pneumatic conveying, there is a problem that the powder leaks to the outside of the crucible through the matching gap between the main / auxiliary pistons and the graphite crucible, which is easy to cause electrical short circuit safety hazards; wherein the high temperature The incubation temperature range is between 1750 and 2150°C or between 1850 and 2150°C; when the high temperature incubation treatment is performed at a temperature above 1850°C, the graphite crucible and the supporting refractory material at the bottom are prone to high temperature reduction reaction, the equipment stability is worrying, and the discharge graphite tube is prone to interference with the crucible; the low temperature incubation temperature range is between 1300-1650°C or 1350-1650°C; in addition, when the artificial graphite powder flows in the spiral cooling flow channel for discharging, local bridging and powder blocking are prone to occur, the discharging has the disadvantage of poor flow, and the production efficiency is not satisfactory.CN202310603657.6 proposes a technical solution of using a spiral quantitative conveyor made of graphite material to directly convey carbon powder raw materials into molten iron, and uses a two-stage gas-solid separation barrier of carbon fiber woven cloth and carbon brushes as a high-temperature gas-solid sealing measure to prevent carbon powder from floating to the outside of the crucible, which can improve the above problems to a certain extent; however, due to the pore size of the carbon fiber woven cloth and the fatigue life of the carbon brush made of carbon fiber, the air permeability and dustproof sealing reliability of the high-temperature sealing material, and how to ensure the safe operation of the equipment are still engineering issues to be improved; using a spiral quantitative conveyor to convey carbon raw material powder into molten iron is likely to cause local compaction and agglomeration of carbon powder, forming microporous agglomerates of carbon powder. After high and low temperature incubation in molten iron, in the subsequent floating and discharging of materials, the carbon powder microporous agglomerates are likely to be mixed with more iron, and the floating is easily inhibited. Even the carbon powder microporous agglomerate-iron mixture after floating adds a lot of workload to the subsequent pickling and iron removal. A common shortcoming of the technical solutions for manufacturing artificial graphite negative electrode materials by high and low temperature molten iron inoculation method in the five invention applications CN202210708922.2, CN202210702022.7, CN202210889452.4, CN202310603657.6, and CN202310735352.0 is that there is a prominent order of contact between the carbon powder raw materials and the molten iron during the feeding process, and the time span of feeding is relatively long, which easily leads to the molten iron dissolving the carbon powder that is contacted first as the feeding proceeds. The carbon content in the molten iron changes dynamically, the wettability of the carbon material powder added later with the molten iron with high carbon content deteriorates, the contact reaction is insufficient, and the consistency of mass-produced products is not easy to ensure.

[0009] The present invention is proposed in view of the many shortcomings and deficiencies of the traditional high-temperature graphitization method for manufacturing artificial graphite negative electrode materials, such as high energy consumption, long growth cycle, high production cost and uneven coating layer; and in view of the problems and deficiencies in the above-mentioned patent applications of the inventors regarding the powder metallurgy method and the high and low temperature molten iron inoculation method for manufacturing artificial graphite negative electrode materials. Summary of the invention

[0010] The present invention proposes a method and device for manufacturing artificial graphite negative electrode materials by molten steel infiltration of porous carbon billets, which is economical and environmentally friendly, has low manufacturing energy consumption, and can complete graphitization and coating deposition in the same device at one time, has a fast production cycle, high raw material utilization rate, stable equipment operation, large gram capacity of artificial graphite products, high initial efficiency, and stable mass production. The technical scheme and production steps are described as follows:

[0011] (1) Put the preheated porous carbon blank into low-carbon molten steel for high-temperature inoculation treatment

[0012] The present invention adopts molten steel with low carbon content as a process medium. The molten steel with low carbon content is located in a crucible inside a vacuum furnace. The molten steel with low carbon content is used to drive a porous carbon blank (hereinafter referred to as porous carbon blank) under vacuum or inert gas protection atmosphere by gas pressure difference to quickly infiltrate the porous carbon blank, thereby realizing a cascade operation of high-temperature inoculation treatment and low-temperature inoculation treatment. Before the porous carbon blank is added to the molten steel with low carbon content for high-temperature inoculation treatment, the initial carbon content in the molten steel is controlled to be between 0.3wt.% and 2.1wt.%, the molten steel is in a carbon-unsaturated state, and the initial temperature of the molten steel is controlled to be between 1550°C and 1750°C. If the carbon content in the molten steel is too low, although the wettability is good, the molten steel will dissolve and consume the carbon in the raw material of the porous carbon blank to the state of carbon-saturated molten iron during the high-temperature inoculation treatment, and the yield of the material will decrease. If the carbon content in the molten steel is too high and becomes molten iron, the liquid-solid interface between the molten iron and the porous carbon blank will be The surface wettability deteriorates, which is not conducive to the overall infiltration of the porous carbon blank. A higher pressure difference is required to drive the porous carbon blank to overcome the osmotic pressure of the porous carbon blank on the molten iron. When feeding, a piston is mechanically lifted in the cavity below it, and the porous carbon blank is fixed in advance with a mesh support plate. The piston and the porous carbon blank block material in the cavity are preheated to 1550°C to 1750°C in the preheating vacuum chamber at the top of the device. The piston moves downward, at least the bottom of the piston is immersed in the molten steel with a low carbon content, and then the gas pressure difference is used to drive the molten steel with a low carbon content to overcome the osmotic pressure of the micro-pores in the porous carbon blank, quickly infiltrate and rise to above the upper plane of the porous carbon blank. The present invention controls the complete infiltration of the porous carbon blank with molten steel within 10 minutes of the gas pressure difference. In order to ensure the uniformity of the product, it is more preferably controlled to achieve complete infiltration of the porous carbon blank with molten steel within 5 minutes of the gas pressure difference, forming a porous carbon blank as shown in the accompanying drawings of the specification. Figure 3 or Figure 5 The schematic diagram shows the state after molten steel infiltrates the porous carbon blank. At this time, the atmosphere pressure P2 is controlled to be greater than the atmosphere pressure P1. The vacuum is used to form a negative pressure at P1, and an inert gas such as nitrogen or argon is introduced at P2 to form a positive pressure between 30 and 300 kPa. After the molten steel level rises to exceed the upper plane of the porous carbon blank, a Figure 3 The height difference of H3 liquid level shown in the figure, or the formation Figure 5The liquid level height difference of H5 indicated in the figure; the present invention performs high-temperature inoculation treatment for 30 to 90 minutes while maintaining the state that the molten steel completely infiltrates the porous carbon blank; before the high-temperature inoculation treatment, the porous carbon blank has a fixed carbon content greater than 99%, and the porous carbon blank mainly uses soft carbon powder raw materials to form a microporous three-dimensional skeleton material, and the content of the soft carbon powder raw materials in the porous carbon blank raw materials is between 70wt.% and 90wt.%, and the remaining raw materials of the porous carbon blank use asphalt as a binder, and the soft carbon powder raw materials include needle coke, low-sulfur petroleum coke, natural graphite, anthracite, and a combination of one or more of coke. The particle size control target of the soft carbon powder raw material is close to the particle size of the finished product of the artificial graphite negative electrode material, and its D95 is less than or equal to 40 microns, the average particle size D50 is greater than or equal to 7 microns, and the fixed carbon content in the soft carbon powder raw material is greater than 99wt.%; asphalt powder is used as a binder for the porous carbon blank Raw materials, the softening point of asphalt powder is between 180℃ and 280℃, the coking value is between 50wt.% and 80wt.%, low temperature crushing or wet ball milling to a particle size D95 less than or equal to 10 microns, more preferably the particle size D95 of the asphalt powder is controlled to be less than or equal to 5 microns, the asphalt powder and the soft carbon powder are mixed evenly and then hot pressed, the process temperature of hot pressing is 20℃ to 100℃ higher than the softening point of the asphalt powder, and the pressure during hot pressing is between 2MPa and 30MPa; after hot pressing, it is subjected to medium temperature carbonization treatment below 1550℃, and a porous carbon blank with a certain strength is formed after carbonization treatment, the volatile matter of the obtained porous carbon blank at 900℃*1 hour is less than or equal to 0.4%, the apparent volume density of the porous carbon blank at room temperature is between 1.15g / cm3 and 1.55g / cm3, and the open porosity of the porous carbon blank is between 52vol.% and 31vol.%, the average pore size of the porous carbon blank in the mercury injection test is between 7 microns and 35 microns; the porous carbon blank needs to control the above technical characteristics of its raw materials and its microporous fine structure based on the following technical considerations: the porous carbon blank has too low an average pore size, which will lead to the need to apply too high a penetration pressure when the molten steel penetrates and infiltrates, posing a challenge to the safety of the equipment; the porous carbon blank has too large an average pore size, which means that a soft carbon powder raw material with too large a particle size is required, which will cause the primary particles of the artificial graphite powder formed after the porous carbon blank is subsequently crushed to be too large, and will not meet the particle size requirements of the artificial graphite negative electrode material. If the particles are crushed twice or multiple times to reduce the particle size and form more fracture cleavage planes, it will affect the specific surface area of ​​the finished artificial graphite powder, and the initial efficiency will be low. , SEI film formation is not uniform enough. The porous carbon blank of the present invention uses pitch powder as a binder, and after carbonization, connects the soft carbon powder into a block material with a three-dimensional microporous structure. The present invention controls the microscopic area of ​​the connection between the particles of the soft carbon powder in the porous carbon blank not to be too large, and the bonding strength of the particle connection is not too high. The technical purpose is to transform the porous carbon blank into a microporous carbon material aggregate mainly composed of artificial graphite powder after high and low temperature cascade inoculation with molten steel. During subsequent pulverization, the microscopic breaking points between the particles of artificial graphite powder are controlled to occur mostly at the weak connection of the particles after the pitch powder is carbonized, and the integrity of the coated core-shell structure of the primary particles of the artificial graphite powder formed after low-temperature inoculation is relatively easy to be guaranteed. .

[0013] During the high-temperature inoculation treatment, the liquid-solid interface between the unsaturated low-carbon molten steel used in the present invention and the numerous micropores of the porous carbon blank in contact with it is in a wet state, and the initial contact angle after 5 minutes is less than 85 degrees. The low-carbon molten steel and the porous carbon blank in contact with it realize two kinds of micro-dissolution reactions: one is that the low-carbon molten steel and the carbon converted after carbonization of the high-activity carbon on the surface of the carbon powder of the porous carbon blank in contact with it and the asphalt bonding part thereof undergo micro-dissolution reaction; the other is that the low-carbon molten steel penetrates into the porous carbon blank through capillary action, wherein the carbon powder is mostly At the grain boundaries inside the crystal, the amorphous carbon, or non-crystalline carbon, at the grain boundaries undergoes a micro-dissolution reaction and local recrystallization caused by concentration fluctuations; as the high-temperature incubation proceeds, the content of dissolved carbon in the high-temperature molten steel gradually rises to more than 2.11wt.% to a saturated state, and the previously unsaturated molten steel process medium becomes a saturated molten iron process medium; in the metallurgical industry, liquid Fe-C high-temperature solutions with a carbon content of less than 2.1wt.% are often called molten steel, and liquid Fe-C high-temperature solutions with a carbon content of more than 2.11wt.% are called molten iron;

[0014] The piston is made of zirconia ceramic material, zirconium carbide ceramic material or graphite material; considering the thermodynamics and kinetics of the high-temperature reduction reaction of carbon element to oxide ceramic during high-temperature inoculation treatment, the crucible of the present invention is sintered with zirconia ceramic material or zirconium carbide-based ceramic material with high high-temperature stability, or zirconia ceramic material or zirconium carbide-based ceramic material is used as the inner lining of the crucible, and graphite material is used as the outer shell of the crucible to form a double-layer composite crucible;

[0015] (2) Low temperature inoculation treatment

[0016] After the high-temperature inoculation treatment, the saturated molten iron and the liquid-solid two-phase mixture of the porous carbon blank after the slight dissolution reaction are cooled to a temperature range of 1250°C to 1450°C, and a low-temperature inoculation treatment process with a cascade process is carried out. The total time for the low-temperature inoculation in the temperature range of 1250°C to 1450°C is between 30 minutes and 180 minutes. During the cooling process and the low-temperature inoculation process, the saturated solubility of carbon in the molten iron gradually decreases, and the supersaturated carbon is gradually precipitated from the molten iron solution. The carbon powder polycrystalline in the porous carbon blank is The carbon elements precipitated at the grain boundaries of the body participate in recrystallization, thereby improving the graphitization degree of the carbon powder; the carbon elements precipitated on the surface of the carbon powder in the porous carbon blank form a carbon coating deposition layer, forming a primary structure of artificial graphite powder with a coated structure, improving the specific surface area of ​​the artificial graphite powder, and improving the uniformity of SEI film formation of the artificial graphite powder in battery applications; after low-temperature incubation treatment, the porous carbon blank is transformed into a microporous aggregate of artificial graphite powder, that is, mainly realizing the improvement of graphitization degree and natural coating of the surface, and the microporous aggregate of artificial graphite powder The wettability between the microporous aggregates of artificial graphite powder and the low-temperature molten iron with high carbon content deteriorates, and the contact angle increases to an obtuse angle greater than 105 degrees in 30 minutes, which is conducive to the subsequent use of gas pressure difference to drive the molten iron with poor wettability to be discharged from the microporous aggregates of artificial graphite powder into the molten iron in the lower crucible, reducing the amount of trace iron elements carried on the surface of the microporous aggregates of artificial graphite powder due to the wetting effect, and reducing the workload for the subsequent pickling and iron removal of artificial graphite powder after crushing; after the low-temperature inoculation treatment is completed, the P1 transformation is set to be greater than P2, and the P2 is changed to In order to evacuate to form negative pressure, inert gas is introduced into P1 to form a positive pressure between 30 KPa and 300 KPa. Under the combined effect of the inert gas pressure difference drive and the deterioration of the wettability of the liquid-solid interface between the molten iron and the microporous aggregates of the artificial graphite powder, the liquid level of the molten iron inside the piston drops to below the lower plane of the microporous aggregates of the artificial graphite powder, and then the piston is lifted upward. The piston carries the microporous aggregates of the artificial graphite powder out of the molten iron in the crucible and goes to the upper preheating vacuum chamber for cooling under the protection of inert gas, and then takes out of the furnace at a temperature below 300°C.

[0017] (3) Post-treatment of microporous aggregates of artificial graphite powder

[0018] The microporous aggregates of the cooled artificial graphite powder are taken out from the piston and moved to the outside of the vacuum furnace for subsequent crushing and pickling. The pickling uses dilute sulfuric acid, dilute nitric acid, or other phosphoric acid or organic acid aqueous solutions that can dissolve iron. The pickling dissolves and removes a small amount of iron mixed in the carbon powder. After cleaning, drying, demagnetization, and particle classification, an artificial graphite powder negative electrode material is formed.

[0019] (4) The molten iron in the crucible is treated with oxygen blowing and decarburization to transform it into molten steel with low carbon content

[0020] After the piston carries the microporous aggregates of artificial graphite powder to the upper preheating vacuum chamber, the flap valve between the preheating vacuum chamber and the lower vacuum furnace is closed, and the carbon-saturated molten iron remaining in the crucible is subjected to oxygen blowing and decarburization treatment. By blowing an appropriate amount of oxygen or a mixed gas of oxygen and inert gas into the carbon-saturated molten iron, part of the carbon elements dissolved in the molten iron solution is oxidized to react and generate carbon monoxide gas, which is discharged to the outside of the vacuum furnace by negative pressure suction; by blowing oxygen into the molten iron for decarburization treatment, the carbon content in the molten iron is adjusted from a saturated state greater than 2.1% to an unsaturated state between 0.3wt.% and 2.1wt.%, and the molten iron is converted into molten steel, and the temperature of the molten steel is adjusted to a temperature range between 1550°C and 1750°C, and a low-carbon molten steel process medium having good liquid-solid interface wettability with the porous carbon blank is re-formed, and then the preheated porous carbon blank is continuously put into the low-carbon molten steel by using the piston, and the above process is repeated to produce the next batch of artificial graphite powder negative electrode materials.

[0021] The technical solution and technical benefits of the present invention are further described below.

[0022] The present invention achieves the following beneficial effects through the above technical scheme and steps: by adding preheated porous carbon blanks into molten steel with low carbon content, rapid infiltration of the molten steel into the porous carbon blanks is achieved under the drive of gas pressure difference, laying a technical foundation for the uniformity of products in subsequent high-temperature inoculation treatment and low-temperature inoculation cascade treatment; after low-temperature inoculation, the molten iron is squeezed out of the microporous aggregates of artificial graphite powder into the molten iron at the bottom by utilizing the combined effect of gas pressure difference and deterioration of wettability of the liquid-solid interface, thereby reducing the workload of subsequent pickling and iron removal after crushing, and also greatly reducing the consumption of molten steel process medium. The method of the present invention is used to manufacture artificial graphite powder negative electrode materials, which has the comprehensive advantages of low material consumption, high production efficiency and low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings in the specification Figure 1 This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by steel water infiltration of porous carbon billet of the present invention. Figure 1 The figure shows that the high and low temperature inoculation treatment has been completed, and the molten iron has been driven by the gas pressure difference to separate from the microporous aggregates of the artificial graphite powder. At this time, the atmosphere pressure P2 above the molten iron liquid surface on the right side of the crucible is lower than the atmosphere pressure P1 on the left side. P2 is in a vacuum atmosphere state to form a negative pressure, and P1 is filled with nitrogen to a positive pressure of 80-100KPa. The molten iron inside the crucible is in a carbon saturated state. Figure 1 1 is a connecting crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a sealing packing; 5 is a pre-pressed porous carbon blank; 6 is a piston; 7 is a preheating vacuum chamber; 8 is a piston water-cooled connecting rod; 9 is a vacuum valve 1; 10 is an intake valve A; 11 is a vacuum valve 2; 12 is a flap valve; 13 is an induction coil B; 14 is an intake valve B; 15 is a vacuum valve 3; 16 is a vacuum valve 4; 17 is carbon-saturated molten iron; 18 is a vacuum furnace; and 19 is a refractory brick support.

[0025] The drawings in the specification Figure 2 This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by steel water infiltration of porous carbon billet of the present invention. Figure 2 The figure shows the state of preparing for high and low temperature inoculation treatment of porous carbon blank, the porous carbon blank is clamped by a ceramic piston and is preheated in a preheating vacuum chamber at the upper part of the device, and the molten steel in the crucible inside the vacuum furnace at the lower part of the device is in a carbon unsaturated state; Figure 2 1 is a connecting crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a sealing packing; 5 is a pre-pressed porous carbon blank; 6 is a piston; 7 is a preheating vacuum chamber; 8 is a piston water-cooled connecting rod; 9 is a vacuum valve 1; 10 is an intake valve A; 11 is a vacuum valve 2; 12 is a flap valve; 13 is an induction coil B; 14 is an intake valve B; 15 is a vacuum valve 3; 16 is a vacuum valve 4; 17 is low-carbon molten steel; 18 is a vacuum furnace; and 19 is a refractory brick support.

[0026] The drawings in the specification Figure 3 This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by steel water infiltration of porous carbon billet of the present invention. Figure 3 The figure shows the state of the porous carbon blank undergoing high-temperature inoculation treatment. The molten steel in the crucible inside the vacuum furnace at the lower part of the device is in a carbon-unsaturated state. The atmosphere pressure P2 above the molten steel liquid level on the right side of the crucible is greater than the atmosphere pressure P1 in the area above the micro-porous carbon blank inside the piston. At this time, P1 is in a vacuumed negative pressure state. Inert gas is used to fill P2 to a positive pressure between 80-90 KPa. The liquid level of the molten steel inside the piston rises to exceed the upper plane of the porous carbon blank, and the height difference with the liquid level in the molten steel inside the crucible on the right is H3; Figure 31 is a connecting crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a sealing packing; 5 is a pre-pressed porous carbon blank; 6 is a piston; 7 is a preheating vacuum chamber; 8 is a piston water-cooled connecting rod; 9 is a vacuum valve 1; 10 is an intake valve A; 11 is a vacuum valve 2; 12 is a flap valve; 13 is an induction coil B; 14 is an intake valve B; 15 is a vacuum valve 3; 16 is a vacuum valve 4; 17 is low-carbon molten steel; 18 is a vacuum furnace; and 19 is a refractory brick support.

[0027] The drawings in the specification Figure 4 This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by molten steel infiltration of porous carbon billets of the present invention, which adopts a single crucible method. Figure 4 The figure shows the state of preparing to carry out high temperature inoculation treatment on the preheated porous carbon blank. The porous carbon blank is clamped by a ceramic piston and has been preheated in the preheating vacuum chamber at the upper part of the device. The lower part of the piston has begun to contact the low-carbon molten steel in the crucible; the molten steel in the crucible inside the vacuum furnace at the lower part of the device is in a carbon-unsaturated state; Figure 4 1 is a crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a sealing packing; 5 is a pre-pressed porous carbon blank; 6 is a piston; 7 is a preheating vacuum chamber; 8 is a piston water-cooled connecting rod; 9 is a vacuum valve 1; 10 is an intake valve 1; 11 is a vacuum valve 2; 12 is an intake valve 2; 13 is a flap valve; 14 is an induction coil B; 15 is a vacuum furnace; 16 is low-carbon molten steel; and 17 is a refractory brick support.

[0028] The drawings in the specification Figure 5 This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by molten steel infiltration of porous carbon billets of the present invention, which adopts a single crucible method. Figure 5 The figure shows the state of the preheated porous carbon blank being subjected to high temperature inoculation treatment. The porous carbon blank has been completely infiltrated by the low-carbon molten steel. The molten steel level inside the piston is above the upper plane of the porous carbon blank. The height difference between the molten steel level inside the piston and the molten steel level inside the crucible and outside the piston is H5; the lower part of the piston is immersed in the low-carbon molten steel in the crucible. At this time, the atmosphere pressure P1 is lower than P2. P1 is kept in a state of vacuuming to form a negative pressure, and P2 is filled with nitrogen to a positive pressure between 110-120KPa; the molten steel in the crucible inside the vacuum furnace is in a carbon-unsaturated state; Figure 5 1 is a crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a sealing packing; 5 is a pre-pressed porous carbon blank; 6 is a piston; 7 is a preheating vacuum chamber; 8 is a piston water-cooled connecting rod; 9 is a vacuum valve 1; 10 is an intake valve 1; 11 is a vacuum valve 2; 12 is an intake valve 2; 13 is a flap valve; 14 is an induction coil B; 15 is a vacuum furnace; 16 is low-carbon molten steel; and 17 is a refractory brick support.

[0029] The drawings in the specification Figure 6This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by molten steel infiltration of porous carbon billets of the present invention, which adopts a single crucible method. Figure 6 The figure shows that the porous carbon blank has been subjected to low-temperature inoculation treatment, and the molten iron is squeezed to the lower part by pressure from the porous carbon blank (which has been transformed into a microporous aggregate of artificial graphite powder), and the height difference between the molten iron level inside the crucible and outside the piston and the molten iron level at the bottom of the piston is H6; the bottom of the piston is immersed in the molten iron in the crucible, and the atmosphere pressure P1 is higher than P2 at this time, and P2 is kept in a state of vacuuming to form a negative pressure, and P1 is filled with inert gas to a positive pressure between 20-30KPa; the molten iron in the crucible inside the vacuum furnace is in a carbon-saturated state; Figure 6 1 is a crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a sealing packing; 5 is a pre-pressed porous carbon blank; 6 is a piston; 7 is a preheating vacuum chamber; 8 is a piston water-cooled connecting rod; 9 is a vacuum valve 1; 10 is an intake valve 1; 11 is a vacuum valve 2; 12 is an intake valve 2; 13 is a flap valve; 14 is an induction coil B; 15 is a vacuum furnace; 16 is carbon-saturated molten iron; and 17 is a refractory brick support.

[0030] The drawings in the specification Figure 7 This is a schematic diagram of the system of the device for manufacturing artificial graphite negative electrode material by molten steel infiltration of porous carbon billets of the present invention, which adopts a single crucible method. Figure 7 The figure shows a state schematic diagram of a porous carbon blank having completed low-temperature inoculation treatment and moved to a preheating vacuum chamber for cooling and then moved to the outside of a vacuum furnace for subsequent treatment, and a ceramic piston is used to blow oxygen and decarburize carbon-saturated molten iron; the bottom of the ceramic piston is immersed in the molten iron in the crucible, and a mixed gas of nitrogen and oxygen is blown into the molten iron; Figure 7 1 is a crucible; 2 is an induction coil A; 3 is a mesh support plate; 4 is a piston; 5 is a preheating vacuum chamber; 6 is a piston water-cooling connecting rod; 7 is a vacuum valve 1; 8 is an air intake valve 1; 9 is a vacuum valve 2; 10 is an air intake valve 2; 11 is a flap valve; 12 is an induction coil B; 13 is a vacuum furnace; 14 is a carbon-saturated molten iron that is decarburized by oxygen blowing to become low-carbon molten steel; 15 is a refractory brick support. DETAILED DESCRIPTION

[0031] The embodiments described below are implemented based on the technical solutions and spirit of the present invention, and provide detailed implementation methods and specific processes, but do not limit the protection scope of the patent of the present invention. Any technical solutions obtained in the form of replacement or equivalent transformation should be understood to fall within the protection scope of the present invention.

[0032] Example 1. A method and device for manufacturing artificial graphite negative electrode material by infiltrating porous carbon billet with steel water, using the attached drawings of the specification Figures 4 to 7The structure shown in the figure has an initial temperature of 1600-1630°C and an initial carbon content of 0.8-0.9%; the pre-pressed porous carbon blank uses needle coke powder as the main raw material, and asphalt powder is used as a binder for hot pressing; the particle size D95 of the needle coke powder is 28 microns, D50 is 16 microns, the true density is between 2.10-2.13 g / cm3, the ash content is less than 0.10wt.%, the volatile matter is less than 0.20wt.%, and the carbon content is greater than 99.3wt.%; the softening point of the asphalt powder is 250°C, the coking value is 72%, the particle size D95 is 8 microns, and the D50 is 4 microns; of the two raw materials, the weight percentage of the needle coke powder is 80%, and the weight percentage of the asphalt powder is 20%; the temperature of hot pressing is 285°C, and the pressure is between 3-8MPa; hot pressing After cooling to room temperature, the porosity of the porous carbon blank was tested by a mercury injection tester and found to be 39%, with an average pore size of 13 microns; the high-temperature incubation temperature was controlled between 1600-1630°C and the insulation time was 50 minutes; the temperature was lowered to 1300-1330°C for low-temperature incubation and the insulation time was 100 minutes; after the low-temperature incubation, the semi-finished block moved up to the preheating vacuum chamber was cooled to below 100°C and removed from the bottom of the piston, and after the block was crushed, it was pickled for 48 hours with 5% dilute sulfuric acid to remove the iron mixed in the semi-finished powder, and after subsequent negative pressure filtration, washing, drying, air flow mill classification, and demagnetization, an artificial graphite negative electrode material was obtained; the true density of the artificial graphite powder was tested to be 2.248 g / cm3, and button batteries were made, and the gram capacity was tested to be between 365-368 mAh / g, with an initial efficiency of 94.8%.

Claims

1. A method for manufacturing artificial graphite negative electrode material by infiltrating porous carbon billet with molten steel, characterized in that: The production steps include the following: (1) Put the preheated porous carbon blank into low-carbon molten steel for high-temperature inoculation treatment The porous carbon blank is rapidly infiltrated by low-carbon molten steel in a vacuum or inert gas protective atmosphere by gas pressure difference driving, so as to realize the cascade operation of high-temperature inoculation treatment and low-temperature inoculation treatment; before the porous carbon blank is added to the low-carbon molten steel for high-temperature inoculation treatment, the initial carbon content in the molten steel is controlled to be between 0.3wt.% and 2.1wt.%, the molten steel is in a carbon unsaturated state, and the initial temperature of the molten steel is controlled to be between 1550℃ and 1750℃; when feeding, the piston is mechanically hoisted in the cavity at the bottom thereof, the porous carbon blank is fixed in advance by a mesh support plate, the piston and the porous carbon blank block material in the cavity are preheated to 1550℃ to 1750℃ in the preheating vacuum chamber at the top of the device, and then the piston moves downward, at least the bottom of the piston is heated to 1550℃ and 1750℃. The porous carbon blank is immersed in low-carbon molten steel, and then the gas pressure difference is used to drive the low-carbon molten steel to overcome the osmotic pressure of the micro-pores in the porous carbon blank, quickly infiltrate and rise to above the upper plane of the porous carbon blank, and the gas pressure difference is controlled to be applied within 10 minutes to achieve complete infiltration of the porous carbon blank by the molten steel. At this time, the atmosphere pressure P2 is controlled to be greater than the atmosphere pressure P1, and a vacuum is used to form a negative pressure at P1, and an inert gas such as nitrogen or argon is introduced at P2 to form a positive pressure between 30 and 300 kPa; the porous carbon blank is kept completely infiltrated by the molten steel for 30 to 90 minutes; before the porous carbon blank is subjected to high-temperature inoculation treatment, its fixed carbon content is greater than 99%, and the porous carbon blank is mainly composed of a microporous three-dimensional skeleton material made of soft carbon powder raw materials The content of soft carbon powder raw materials in the porous carbon blank raw materials is between 70wt.% and 90wt.%, and the remaining raw materials of the porous carbon blank use asphalt as a binder. The soft carbon powder raw materials include needle coke, low-sulfur petroleum coke, natural graphite, anthracite, and a combination of one or more of coke. The particle size control target of the soft carbon powder raw materials is close to the particle size of the finished product of the artificial graphite negative electrode material, and its D95 is less than or equal to 40 microns, the average particle size D50 is greater than or equal to 7 microns, and the fixed carbon content in the soft carbon powder raw materials is greater than 99wt.%; asphalt powder is used as a binder raw material for the porous carbon blank, the softening point of the asphalt powder is between 180℃ and 280℃, and the coking value is between 50wt.% and 80wt.%, and low-temperature crushing or wet ball milling is performed. The particle size D95 is less than or equal to 10 microns. The asphalt powder and the soft carbon powder are mixed evenly and then hot-pressed. The process temperature of the hot-pressing is 20°C to 100°C higher than the softening point of the asphalt powder. The pressure during the hot-pressing is between 2MPa and 30MPa. After the hot-pressing, the hot-pressing is subjected to a medium-temperature carbonization treatment below 1550°C. After the carbonization treatment, a porous carbon blank block with a certain strength is formed. The volatile content of the obtained porous carbon blank at 900°C*1 hour is less than or equal to 0.4%. The apparent volume density of the porous carbon blank at room temperature is between 1.15 g / cm3 and 1.55 g / cm3. The open porosity of the porous carbon blank is between 52 vol.% and 31 vol.%. The average pore size of the porous carbon blank in the mercury injection test is between 7 microns and 35 microns. During the high-temperature inoculation treatment, the liquid-solid interface between the unsaturated low-carbon molten steel and the numerous micropores of the porous carbon blank in contact with it is in a wetting state, and the initial contact angle after 5 minutes is less than 85 degrees. The low-carbon molten steel and the porous carbon blank in contact with it realize two micro-dissolution reactions: one is that the low-carbon molten steel and the high-activity carbon on the surface of the carbon powder of the porous carbon blank in contact with it and the carbon converted after carbonization at the asphalt bonding part undergo micro-dissolution reaction; the other is that the low-carbon molten steel penetrates into the porous carbon blank through capillary action, and the amorphous carbon, or non-crystalline carbon, at the grain boundaries inside the carbon powder polycrystals undergoes micro-dissolution reaction and local recrystallization caused by concentration fluctuations; as the high-temperature inoculation proceeds, the content of dissolved carbon in the high-temperature molten steel gradually rises to more than 2.11wt.% to a saturated state, and the previously unsaturated molten steel process medium becomes a saturated molten iron process medium; (2) Low temperature inoculation treatment After the high-temperature inoculation treatment, the saturated molten iron and the liquid-solid two-phase mixture of the porous carbon blank after the slight dissolution reaction are cooled to a temperature range of 1250°C to 1450°C, and a low-temperature inoculation treatment process cascaded in the process is carried out. The total time for the low-temperature inoculation in the temperature range of 1250°C to 1450°C is between 30 minutes and 180 minutes. During the cooling process and the low-temperature inoculation process, the saturated solubility of carbon in the molten iron gradually decreases, and the supersaturated carbon is gradually precipitated from the molten iron solution. The carbon powder in the porous carbon blank is mostly The carbon elements precipitated at the crystal boundaries participate in recrystallization, thereby improving the graphitization degree of the carbon powder; the carbon elements precipitated on the surface of the carbon powder in the porous carbon blank form a carbon coating deposition layer, forming a primary structure of artificial graphite powder with a coated structure, improving the specific surface area of ​​the artificial graphite powder, and improving the uniformity of SEI film formation of the artificial graphite powder in battery applications; after low-temperature incubation treatment, the porous carbon blank is transformed into a microporous aggregate of artificial graphite powder, that is, mainly realizing the improvement of graphitization degree and natural coating of the surface, and the microporous The wettability between the aggregates and the low-temperature molten iron with a high carbon content deteriorates, and the contact angle increases to an obtuse angle greater than 105 degrees in 30 minutes. Subsequently, the gas pressure difference is used to drive the molten iron with poor wettability to be discharged from the microporous aggregates of the artificial graphite powder into the molten iron in the lower crucible, thereby reducing the amount of trace iron elements carried on the surface of the microporous aggregates of the artificial graphite powder due to the wetting effect, thereby reducing the workload for the subsequent pickling and iron removal work of the artificial graphite powder after crushing; after the low-temperature inoculation treatment is completed, the P1 transformation is set to be greater than P2, and P2 is changed to Vacuuming to form negative pressure, and introducing inert gas at P1 to form a positive pressure between 30KPa and 300KPa. Under the combined effect of the inert gas pressure difference drive and the deterioration of the liquid-solid interface wettability of the molten iron and the microporous aggregates of the artificial graphite powder, the liquid level of the molten iron inside the piston drops to below the lower plane of the microporous aggregates of the artificial graphite powder, and then the piston is lifted upward. The piston carries the microporous aggregates of the artificial graphite powder out of the molten iron in the crucible and goes to the upper preheating vacuum chamber for cooling under the protection of inert gas, and then takes out of the furnace at a temperature below 300°C. (3) Post-treatment of microporous aggregates of artificial graphite powder The microporous aggregates of the cooled artificial graphite powder are taken out from the piston and moved to the outside of the vacuum furnace for subsequent crushing and pickling. The pickling uses dilute sulfuric acid, dilute nitric acid, or other phosphoric acid or organic acid aqueous solution that can dissolve iron. The pickling dissolves and removes a small amount of iron mixed in the carbon powder. After washing, drying, demagnetization, and particle classification, an artificial graphite powder negative electrode material is formed; (4) The molten iron in the crucible is treated with oxygen blowing and decarburization to transform it into molten steel with low carbon content After the piston carries the microporous aggregates of artificial graphite powder to the upper preheating vacuum chamber, the flap valve between the preheating vacuum chamber and the lower vacuum furnace is closed, and the carbon-saturated molten iron remaining in the crucible is subjected to oxygen blowing and decarburization treatment. By blowing an appropriate amount of oxygen or a mixed gas of oxygen and inert gas into the carbon-saturated molten iron, part of the carbon elements dissolved in the aqueous iron solution are oxidized to react and generate carbon monoxide gas, which is discharged to the outside of the vacuum furnace by negative pressure suction; by blowing oxygen into the molten iron for decarburization treatment, the carbon content in the molten iron is adjusted from a saturated state greater than 2.1% to an unsaturated state between 0.3wt.% and 2.1wt.%, and then converted into molten steel, and the temperature of the molten steel is adjusted to a temperature range between 1550°C and 1750°C, and a low-carbon molten steel process medium with good liquid-solid interface wettability with the porous carbon blank is re-formed, and then the preheated porous carbon blank is continuously put into the low-carbon molten steel by using a piston, and the above process is repeated to produce the next batch of artificial graphite powder negative electrode materials.

2. The method according to claim 1, the device for manufacturing artificial graphite negative electrode material by infiltration of porous carbon billet with steel water, characterized in that: The device for manufacturing artificial graphite negative electrode material by infiltrating porous carbon billet with molten steel adopts a single crucible method, mainly including an independent crucible located inside a vacuum furnace, an induction coil A for induction heating the molten steel; a mesh support plate at the bottom of the piston; a sealing packing of the solid porous carbon billet; a ceramic piston located at the center of the crucible; a preheating vacuum chamber at the top of the vacuum furnace; a piston water-cooling connecting rod for controlling the up and down displacement movement of the ceramic piston; a vacuum valve and an air intake valve for adjusting the atmosphere pressure inside the piston, and a vacuum valve and an air intake valve for adjusting the atmosphere pressure above the molten steel liquid level between the inside of the crucible and the outside of the piston.

Citation Information

Patent Citations

  • Medium-temperature graphitized artificial graphite negative electrode material and manufacturing method thereof

    CN114614001A

  • Medium-temperature graphitized artificial graphite negative electrode material and manufacturing method thereof

    CN114620719A

  • Molten iron-assisted graphitized artificial graphite negative electrode material and manufacturing method thereof

    CN114804091A

  • Pulse current internal heating type medium-temperature graphitized negative electrode material and manufacturing method thereof

    CN114804877A

  • Molten iron inoculated artificial graphite negative electrode material and manufacturing method thereof

    CN115028164A